ICOS ATC CO2 Release from Svartberget (150.0 m), 2017-06-01–2026-03-31 - Eric Larmanou; Per Marklund; Mikaell Ottosson-Löfvenius; Paul Smith (Integrated Carbon Observation System, 2026)
Quality-controlled data on molar fraction of atmospheric CO2
All the time series have been updated due to a Flask and Calibration Laboratory minor internal scale update. The revision of CO2 data has been made to account for the response difference of isotopologue selective analyzers to the differences of d13C and d18O in CO2 of references gases compared to ambient air CO2 (see: Jordan A. (2024): Accounting for CO2 isotopic composition inhomogeneity in standard gases used for isotopologue specific CRDS measurements , https://community.wmo.int/events/22nd-wmoiaea-meeting-carbon-dioxide-other-greenhouse-gases-and-related-tracers-measurement)
Larmanou, E., Marklund, P., Ottosson-Löfvenius, M., Smith, P. (2026). ICOS ATC CO2 Release from Svartberget (150.0 m), 2017-06-01–2026-03-31, ICOS RI, https://hdl.handle.net/11676/NKFIbVC7MskIOLsW_vDFHQXc
Keywords: Atmosphere Thematic Centre; CO2; ICOS; dry air mole fraction; time instant, UTC; time instant, UTC; CO2 (dry air mole fraction); CO2 (dry air mole fraction); standard deviation of gas mole fraction; standard deviation of gas mole fraction; quality flag; quality flag; number of points; number of points; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap